Introducción al pensamiento estético de María Zambrano: Algunos lugares de la pintura - Micheron, Cécile (Logos. Anales del Seminario de Metafísica, 2003)
María Zambrano art critic presents the special space that painting was for her. Transcribing her contemplations, she reveals an appropriate way to enter in the pictures: the poetic reason, which constitutes a new aesthetic based on fidelity to original reality and on the revelation of a presence. Zambrano defines painting as a creative act that bursts out of the artist odyssey towards his entrails and to the revelation always incomplete of the original reality. We want to understand the expression of the enigmatic presence by the art of painting and by the poetic reason, through the analysis of the coherence between the principles of Zambrano aesthetic and her own art critic. The auroral motives of painting and the auroral metaphors of poetic reason take up the challenge of the ineffable presence receiving it in a form that becomes promise of transcendence and of revelation for the contemplator and the reader. The motif of the fire in Saint Barbara by the Master of Flemalle and its contemplation transcribed by Zambrano accompany us with the same intensity. Poetic reason constitutes an aesthetic because it stands in a radical plane of liberty-obedience, opening the door of the human paradox, centre of revelation and of creation.